2003
DOI: 10.1002/chem.200204356
|View full text |Cite
|
Sign up to set email alerts
|

A Distinctive Example of the Cooperative Interplay of Structure and Environment in Tuning of Intramolecular Charge Transfer in Second‐Order Nonlinear Optical Chromophores

Abstract: The strongly enhanced cooperative influence of medium polarity and organic structural design on the first hyperpolarizability beta of a novel family of highly polarizable azinium-(CH=CH-thienyl)-dicyanomethanido chromophores 1-3 is described. The dyes can be efficiently synthesized by regioselective protonation/alkylation of the corresponding bidentate anion precursors. Consecutive annelation of the pyridyl ring of 1 (pyridine-->quinoline-->acridine) and medium polarity effects are responsible for an extraordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
86
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(99 citation statements)
references
References 69 publications
6
86
1
6
Order By: Relevance
“…Equation (1) describes two possible limiting forms of acceptor/ donor-substituted polyenes and, therefore, cannot be used for merocyanines. Equation (2) (4) and (5) do not represent polyene-like forms as often claimed, [4,6,[9][10][11][12] but are equivalent to structure b in Equation (3) for cyanines and are polymethines.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Equation (1) describes two possible limiting forms of acceptor/ donor-substituted polyenes and, therefore, cannot be used for merocyanines. Equation (2) (4) and (5) do not represent polyene-like forms as often claimed, [4,6,[9][10][11][12] but are equivalent to structure b in Equation (3) for cyanines and are polymethines.…”
mentioning
confidence: 93%
“…The concepts of the average bond-length alternation (BLA), [7] and the closely related average p-bond order alternation (BOA), [8] between adjacent bonds in the hydrocarbon chain are most popular. [4,6,[9][10][11][12]] Surprisingly, within the same concept merocyanines have been described by two quite different models, namely Equations (1), [7a,c, 8b,c] and (2), [7b, 8a] in which A (electron acceptor) and D (electron donor) are capable of charge exchange. Polymethines are characterized by a chain of conjugated double bonds with an odd number n of p centers and (n + 1) p electrons, whereas polyenes are characterized by an even number of p centers and the same number of p electrons.…”
mentioning
confidence: 99%
“…[138,139] Neue Ansätze in präparativer Hinsicht bieten Sternverbindungen (Abschnitt 3.3) [140] und dipolare Strukturen wie 101, bei denen -im Unterschied zu der bei 2 im Schema 3 beschriebenen Mesomerie -aromatische und dipolare Resonanzstrukturen vereinbar sind (Schema 30). [141] Das vielversprechende Ziel sind schlussendlich maßgeschneiderte D-p-A-Strukturen (molecular engineering) für bestimmte elektrooptische Anwendungen wie die optische Datenspeicherung, Datenverarbeitung und Datenübertragung. [142] Für die Förderung der im Artikel zitierten eigenen Arbeiten bedanke ich mich bei der Deutschen Forschungsgemeinschaft, bei der Volkswagen-Stiftung, beim Fonds der Chemischen Industrie und beim Materialwissenschaftlichen Forschungszentrum der Universität Mainz.…”
Section: Zusammenfassung Und Ausblickunclassified
“…76 In the search for push-pull conjugated compounds promising in the design of NLO materials, dyes 41-43 were investigated. 51,77,78 It was observed that the quinoid character of 41-43 increases with higher annelation, i.e., in the order 41 < 42 < 43.…”
mentioning
confidence: 99%
“…Dyes 41-43 give access to large second-order molecular NLO activities, provided the solvent polarity is suitable (Scheme 21). 77 Organic transition metal complexes may combine redox or magnetic behavior with NLO properties, a fact interesting for construction of multifunctional materials. It was established that some ruthenium pyridyl ammines containing pyridine groups often have very high b o values, associated with intense, low energy metal-to-ligand CT (MLCT) excitations.…”
mentioning
confidence: 99%